Formulation and Evaluation of Gliclazide in Vegetable Oil-Based Self Emulsifying Delivery System - Gehan F. Balata (Journal of Applied Pharmaceutical Science, 2018)
Objectives: To formulate a poorly water-soluble, antidiabetic drug, gliclazide, in the vegetable oil-based self-emulsifying delivery system (SEDDS), as a trial to improve its dissolution and hence its bioavailability. Material and methods: Solubility of gliclazide was investigated in different vegetable oils, surfactants and co-surfactants. The system was selected and the self-emulsification region was identified. Drug-loaded SEDDS was prepared and evaluated in terms of emulsification time, phase separation, droplet size and rate of drug dissolution. The formulation that showed good self-emulsifying properties, acceptable droplet size and high % drug release was further processed into solid- SEDDS by physical mixing with varying proportions of a mixture (2:1) of microcrystalline cellulose and lactose and characterized for crystalline, droplet size and in vitro drug dissolution properties. Results and Conclusions: Formulation of gliclazide in liquid and solid SEDDS using olive oil resulted in significant (P < 0.05) improvement in its dissolution properties. Both differential scanning calorimetry and x-ray diffraction studies demonstrated the presence of gliclazide in the molecular state in all the prepared solid formulations. Solid SEDDS of gliclazide containing a lower proportion of adsorbent (G1) had comparable dissolution properties with its liquid form. Thus formulation of gliclazide in the solid self-emulsifying system may be a promising strategy to improve its dissolution properties.
Keywords: Gliclazide, solid-SEDDS, ternary phase diagram, dissolution, olive oil.